Understanding Intersectionality: an Analysis of Gender, Class, and Ethnicity in The Film Hati Suhita - Sri Lestari; Hubbi Saufan Hilmi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
The interaction of gender, class, and ethnicity shapes representations of women within social contexts. This study investigates the intersections of gender, class, and ethnicity in the film Hati Suhita and their impacts on character portrayal and narrative conflict. Employing a qualitative descriptive approach, data were collected via library research and systematic viewing with detailed note-taking; validity was secured through theoretical triangulation. Data were analyzed using thematic techniques alongside Miles and Huberman’s interactive model. The research questions were addressed by evaluating the interactions among the three variables and their effects on character representation and emergent conflicts. Findings indicate that gendered intersections manifest in expectations of domestic labour and the endurance imposed on the female protagonist in her role as wife; class intersections are evident in her positional authority as a member of the pesantren elite, conferring leadership and mediatory capacities in intergenerational familial disputes; and ethnic-cultural intersections appear through spiritual practices—such as tabarukan, uzlah, and pilgrimage to revered graves—which function as religious coping strategies in response to emotional strain and domestic discord. Thus, the film demonstrates that women’s lived experiences cannot be comprehended solely through gender categories but must be read through the simultaneous confluence of multiple social and cultural identities that shape how individuals perceive, respond to, and negotiate their realities. These findings contribute to scholarship on intersectionality in arts and culture and underscore the necessity of layered analytical frameworks in film studies.